EFFECT OF ENVIRONMENT ON GALAXIES' MASS-SIZE DISTRIBUTION: UNVEILING THE TRANSITION FROM OUTSIDE-IN TO INSIDE-OUT EVOLUTION - Cappellari, M (2013)
The distribution of galaxies on the mass-size plane as a function of redshift or environment is a powerful test for galaxy formation models. Here we use integral-field stellar kinematics to interpret the variation of the mass-size distribution in two galaxy samples spanning extreme environmental densities. The samples are both identically and nearly mass-selected (stellar mass M * ≳ 6 × 109 M⊙) and volume-limited. The first consists of nearby field galaxies from the ATLAS3D parent sample. The second consists of galaxies in the Coma Cluster (Abell 1656), one of the densest environments for which good, resolved spectroscopy can be obtained. The mass-size distribution in the dense environment differs from the field one in two ways: (1) spiral galaxies are replaced by bulge-dominated disk-like fast-rotator early-type galaxies (ETGs), which follow the same mass-size relation and have the same mass distribution as in the field sample; (2) the slow-rotator ETGs are segregated in mass from the fast rotators, with their size increasing proportionally to their mass. A transition between the two processes appears around the stellar mass M crit ≈ 2 × 1011 M ⊙. We interpret this as evidence for bulge growth (outside-in evolution) and bulge-related environmental quenching dominating at low masses, with little influence from merging. In contrast, significant dry mergers (inside-out evolution) and halo-related quenching drives the mass and size growth at the high-mass end. The existence of these two processes naturally explains the diverse size evolution of galaxies of different masses and the separability of mass and environmental quenching. © 2013. The American Astronomical Society. All rights reserved.